Highly Stretchable and UV Curable Elastomers for Digital Light Processing Based 3D Printing - Patel, Dinesh K (Advanced materials (Deerfield Beach, Fla.), 2017)
© 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.